Cold feet: trackways and burrows in ice-marginal strata of the end-Ordovician glaciation (Table Mountain Group, South Africa) - Davies, NS; Shillito, AP; Penn-Clarke, CR (GeoScienceWorld, 2020)
New observations from an outcrop of Upper Ordovician Table Mountain Group strata (Matjiesgoedkloof, Western Cape Province, South Africa) have revealed an unexpected ichnofauna that is hosted within diamictites and sandstones that were deposited by a retreating low-latitude (∼30°S) ice sheet during the Hirnantian glaciation. The locality provides a rare window onto animal-sediment interactions in an early Paleozoic ice-marginal shallow-marine environment and contains a trace fossil community with a surprising ichnodiversity and ichnodisparity of burrows, trackways, and trails (Archaeonassa, Diplichnites, Heimdallia, Metaichna, ?Multina, Planolites, Protovirgularia, Skolithos). Exceptional phenomena preserved in the strata include evidence for direct colonization of glacial diamictites by deep-burrowing Heimdallia infauna, and interactions between trackways and dropstones on substrates. Observations from the newly recognized outcrop dramatically expand our understanding of deep-time glacial habitats, demonstrating that deglaciating ice margins had already been colonized by the latest Ordovician. The freshwater influx that would have been associated with such settings implies that faunal associations that were tolerant of brackish water were also established by that time. The locality has further significance because it records the activity of a nearshore animal community contemporaneous with the fauna of the nearby Soom Shale lägerstatte. Combined, these features reveal a paleoecological transect of the diverse marine life that inhabited cold-climate, low-latitude shallow seas around the time of the end-Ordovician deglaciation.